2015
DOI: 10.5301/jbm.5000142
|View full text |Cite
|
Sign up to set email alerts
|

Possible role for interleukins as biomarkers for mortality and recurrence in oral cancer

Abstract: Abstract:Objectives: Salivary and serum levels of interleukin-6 (IL-6) and interleukin-8 (IL-8) have previously been studied in oral cancer with conflicting results. Methods: We designed a controlled study to assess the correlation between pretreatment salivary and serum levels of IL-6 and IL-8, and all-cause survival and cancer recurrence in oral cancer patients. Results: Fifty-two oral cancer patients and 52 healthy control cases were selected. In univariate analysis, salivary IL-6 and IL-8 seemed to be more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 14 publications
5
21
0
Order By: Relevance
“…There is clear evidence that proinflammatory growth factors play a vital role in cancer development and progression . However, clinical studies investigating serum levels of proinflammatory growth factors and cytokines are rare.…”
Section: Discussionmentioning
confidence: 99%
“…There is clear evidence that proinflammatory growth factors play a vital role in cancer development and progression . However, clinical studies investigating serum levels of proinflammatory growth factors and cytokines are rare.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported [ 16 ], all subjects were asked to refrain from: eating, drinking, or oral hygiene for at least one hour prior to collection (usually between 9 and 11 a.m.); they then rinsed their mouths with water and then waited for at least 5 min before spitting into a 50 ml Falcon tube. Participants were instructed not to cough or forcefully expectorate in order to collect unstimulated saliva samples.…”
Section: Methodsmentioning
confidence: 99%
“…Several previous studies have shown that both increased systemic CRP levels [ 8 , 47 , 48 , 49 , 50 , 51 , 52 ] and IL6 levels [ 9 , 21 , 22 , 23 , 53 , 54 , 55 , 56 , 57 ] are associated with an adverse prognosis in HNSCC. IL6 can function as a driver of the acute phase reaction, i.e., increased CRP levels can at least partly be due to an IL6 effect [ 1 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory parameters are considered as possible prognostic markers in several human malignancies [ 9 , 55 ]. These parameters include both acute phase proteins and peripheral blood concentrations of various leukocyte subsets and platelets [ 62 , 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation